Factors affecting hybrid car purchase intention in Malaysia - Woon, Yaw Hor; Hishamuddin, Ismail; Rahman, Muhammad Sabbir (2014)
The paradox between mobility of private transport and the consumption of petrol poses difficulty for the Government to maintain living standard without the expense of environmental pollution. The capital used in petrol subsidies may backlash the continuous improvement for the nation. These national capital may failed to benefit particular segment of population. Saving from the subsidies could build more infrastructure and public facilities. Hybrid car, which viewed as the most feasible alternative to replace conventional car, could significantly reduce the aggregate volume of petrol consumption through advance technologies. This paper aimed to investigate the compatibility of Theory of Planned Behaviour in explaining the green product with high customer involvement during the pre-purchase stage. Especially after the introduction of NAP 2014, the strong internal demand for hybrid car could facilitate the supply side strategies to solidify Malaysia’s position as the regional marketing and production hub for energy efficient vehicle. A structured, closed-ended questionnaire was used and targeted the existing car owners as the subject of study. Overall, this paper confirmed the role of TPB in explaining the purchase intention of high involvement green product through the construct of subjective norm, perceived behavioural control, and attitude with the moderation of age.